THE INFLUENCE OF GREEN HOSPITAL PRACTICES AND MEDICAL WASTE MANAGEMENT EFFICIENCY ON HOSPITAL IMAGE - Melinia Cahaya Fitri; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Environmental sustainability has become a critical concern in healthcare institutions, where hospitals generate significant amounts of waste and consume large volumes of energy and resources. This study reviews the literature on the influence of green hospital practices and efficient medical waste management on hospital image. A systematic review of five recent studies published between 2024 and 2026 was conducted, focusing on sustainable hospital management strategies, pharmaceutical and domestic waste management, and eco-efficiency initiatives. The findings indicate that the implementation of green hospital practices including energy efficiency, sustainable resource utilization, environmentally friendly infrastructure, and waste minimization contributes significantly to operational sustainability. Efficient medical waste management, supported by structured systems, staff training, and policy enforcement, reduces environmental risks and ensures regulatory compliance. Moreover, hospitals that adopt these practices demonstrate greater social responsibility, which enhances their public image, fosters patient trust, and strengthens stakeholder perceptions. In conclusion, green hospital practices and efficient medical waste management are essential for sustainable healthcare operations. They not only reduce environmental impact and improve operational efficiency but also serve as strategic tools for enhancing hospital reputation. Institutional commitment, continuous education, and policy integration are key factors for achieving effective environmental management in healthcare settings.